Trauma, Resilience, and Health Promotion in LGBT Patients What Every Healthcare Provider Should Know - Eckstrand, Kristen L.; Potter, Jennifer; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book has two goals: to educate healthcare professionals about the effect of identity-based adversity on the health of their LGBT patients, and to outline how providers can use the clinical encounter to promote LGBT patients$1 (Bresilience in the face of adversity and thereby facilitate recovery. Toward this end, it addresses trauma in LGBT populations; factors that contribute to resilience both across the lifespan and in specific groups; and strategies for promoting resilience in clinical practice. Each chapter includes a case scenario with discussion questions and practice points that highlight critical clinical best practices. The editors and contributors are respected experts on the health of LGBT people, and the book will be a (3z(Bfirst of its kind(3y (Bresource for all clinicians who wish to become better educated about, and provide high quality healthcare to, their LGBT patients.s
PART 1: OVERVIEW OF TRAUMA IN LGBT POPULATIONS -- 1.Intersection of Trauma and Identity -- 2.Medical Intervention and LGBT People: A Brief History -- 3.Conceptualizing Trauma in Clinical Settings: Iatrogenic Harm and Bias -- 4.Impact of Stress and Strain on Current LGBT Health Disparities -- PART 2: RESILIENCE ACROSS THE LIFESPAN -- 5.The Role of Resilience and Resilience Characteristics in Health Promotion -- 6.Childhood and Adolescence -- 7.Resilience Across the Lifespan: Adulthood -- 8.Older Adults -- PART 3: RESILIENCE IN SPECIFIC POPULATIONS -- 9.Transgender and Gender Nonconforming Individuals -- 10.Understanding Trauma and Supporting Resilience with LGBTQ People of Color -- 11.LGBT Forced Migrants -- 12.Lesbian and Bisexual Women -- 13.Institutionalization and Incarceration of LGBT Individuals -- PART 4: RESILIENCE PROMOTION IN CLINICAL PRACTICE -- 14.An Overview of Trauma-Informed Care -- 15.Screening and Assessment of Trauma in Clinical Populations -- 16.Patients and their Bodies: The Physical Exam -- 17.Motivational Interviewing for LGBT Patients -- 18.Promoting Healthy LGBT Interpersonal Relationships -- 19.Community Responses to Trauma -- 20.Resilience Development among LGBT Health Practitioners.
Keywords: Medicine; General practice (Medicine).; Primary care (Medicine).; Psychotherapy; Medicine & Public Health; General Practice / Family Medicine; Primary Care Medicine; Psychotherapy